Book Review: Global Warming - Nadia Astriani (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2015)
Global Warming is part of Greenhaven’s Contemporary Issues Companion series published by, Thomson Gale on 2005. Each volume of the anthologyseries focuses on a topic of current interest, presenting informative and thought-provoking selection written from wide-variety viewpoints. It is an ideal launching point for research on a particular topic. Each anthology in the series is composed of readings taken from an extensive gamut of resources, including periodical, newspapers, books, governmentdocuments, the publications of private and public organization an internet website. Readers will find factual support suitable for use in reports, debate, speeches and research papers. In understanding Environmental Law, student must understand the environmental issues first. Global warming is the latest issue in Environmental Law field, it has been discuss for more than a decade. It is hard for law student, who don’t have any scientific background to understand this issue. That’s why this anthology series is perfect start for student to understanding Global Warming Issue. This book consist of three part, namely: Understanding Global Warming, The Consequences of Global warming and Solving the Global warming Problem. Each chapter contains 6-7 articles.  DOI: https://doi.org/10.22304/pjih.v2n1.a11